A dataset of expression profile of certain microRNAs in Caenorhabditis elegans - Yimeng Gao; Yuchuan Bai; Shipeng Hu; Zhiju Tao; Yiru Jiang; Di Zhao (Scientific Data)
Abstract MicroRNAs (miRNAs), as crucial gene regulatory molecules, participate in the regulation of biological processes through multiple mechanisms such as transcriptional repression and mRNA degradation. In this study, we first examined the expression patterns of 36 miRNAs at the L1 stage of Caenorhabditis elegans (C. elegans), revealing that the majority exhibited basal low expression levels. To investigate the evolutionary conservation of miRNAs, we selected Caenorhabditis briggsae (C. briggsae), which shares similar embryonic-to-L1-stage cell lineages with C. elegans but is taxonomically distinct, and constructed 15 miRNA reporter strains for cross-species comparison. Additionally, to elucidate the regulatory role of miRNAs in development, we generated single-gene mutants and multi-gene combinatorial mutants targeting miRNAs specifically expressed in excretory cells and quantified the phenotypic variations in excretory cells across different miRNA mutant combinations. The comprehensive dataset provided in this study will serve as a valuable resource for subsequent miRNA functional studies and candidate gene screening, thereby advancing our understanding of miRNA regulatory networks.